Aprimoramento normativo do sistema de alertas de desastres naturais no município de Belém. - BRITO, Wagner Lobato (Universidade Federal do Pará, 2019)
The democratic state of Brazilian law has been evolving significantly in the improvement of legislation related to the management of risk minimization and mitigation of natural disasters. However, there is a lack of concrete normative provisions that regulate the municipal institution of an effective and effective system for the transmission of the alerts to the Civil Defense of the municipality of Belém, in order to minimize and even mitigate the risks of natural disasters and thus safeguard the vulnerable population. The need for a more robust and effective legal mechanism becomes clear when the impacts caused by natural disasters in the capital of the state of Pará are analyzed, as well as the communities that are affected and the population that is in imminent danger. The present study has as main objective the proposal of a normative tool of municipal civil defense, for Bethlehem, with the intention of prevention and mitigation of risks to natural disasters. In the region of study, natural disasters such as windstorms, floods and floods are frequent. It is known that the causes for occurrence of these events come from natural phenomena and their events are neither transient nor punctual. The methodological procedures consisted of analyzes of the current legislation related to the subject, at the federal, state and municipal level, as well as important information of the monitoring system of alerts and natural disasters, which served as reference to plan the elucidation of its execution, organization and legal analysis. Also analyzed were the hierarchies of the laws, characterizing the constitutionality of the norms and the legal powers that authorize and delegate the creation of normative instruments that regulate the system of monitoring and alerts of natural disasters. The product of the research is the elaboration of the draft of the proposal of amendment of the municipal Law, more precisely with regard to art. 5, item "F", to make the use of the alert tool made available by the monitoring institutions by the municipal Civil Defense agency dynamic and mandatory.